Beyond justices: The legal culture of judges in Mexico - Azul América Aguiar Aguilar (German Institute of Global and Area Studies (GIGA), 2020)
Judges' ideas, beliefs, and values are central to adjudication. Empowering the courts was a crucial step in third-wave democracies and, after some unfulfilled promises regarding the potential of the judicialization of politics for rights expansion, we need to learn more about the individuals that were empowered and what their legal culture can tell us about judicial behavior. Do judges consider themselves political actors having a legislative role? What type of legal culture do they have? To advance our understanding of these key determinants of judicial behavior, I use a survey with federal judges in Mexico to explore to what extent judges adhere to a positivist or a principle-based constitutionalist legal culture. Findings suggest that there is a tension in the judiciary, with some judges embracing the idea of legislating from the bench while others prefer to play the role of being "the mouthpiece of the law.
Keywords: 300; Rechtsordnung; Soziale Werte; Rechtsberufe; Rechtsstaat; Mexiko